Aspirin withdrawal in patients treated with ticagrelor presenting with non‐ST elevation myocardial infarction. (15th March 2018) - Beigel, R.; Mazin, I.; Koifman, E.; Shechter, M.; Pres, H.; Shlomo, N.; Rosenberg, N.; Asher, E.; Matetzky, S.
Abstract : Essentials Strong P2Y12 blockade may cause platelet inhibition that is only minimally enhanced by aspirin. We evaluated aspirin withdrawal on platelet reactivity in ticagrelor treated patients. Aspirin withdrawal resulted in increased platelet reactivity to arachidonic acid. Aspirin withdrawal caused little difference in adenosine diphosphate‐induced platelet aggregation. Summary: Background: Recent studies have shown that the thromboxane A2 ‐dependent pathway is dependent on the ADP–P2Y12 pathway, and that strong P2Y12 receptor blockade alone causes inhibition of platelet aggregation that is minimally enhanced by aspirin. Data from the PLATO trial suggested that, among ticagrelor‐treated patients, high‐dose versus low‐dose (< 100 mg day −1 ) aspirin is associated with an increased risk fof ischemic events. Objectives: To evaluate the impact of aspirin withdrawal on platelet reactivity in acute coronary syndrome (ACS) patients treated with a potent P2Y12 blocker. Patients/Methods: This was a current prospective, randomized, placebo‐controlled, double‐blind, cross‐over study. The study population comprised 22 consecutive ACS patients who underwent percutaneous coronary intervention and were treated with aspirin (100 mg day −1 ) and ticagrelor. Thirty days post‐ACS, open‐label aspirin was stopped, and patients were randomized to either blinded aspirin or placebo for 2 weeks, with each patient crossing over to the other arm for an additional 2 weeks. Platelet reactivity to arachidonic acid and ADP determined with light‐transmission aggregometry (LTA) and VerifyNow was evaluated at baseline, and 2 weeks and 4 weeks later. Results: Aspirin withdrawal resulted in an increase in arachidonic‐acid induced platelet reactivity as determined with both LTA (77.0% ± 11.3% versus 20.8% ± 4.4%) and VerifyNow (607.7 ± 10.6 aspirin reaction units [ARU] versus 408.5 ± 14.4 ARU). Platelet response to ADP, as determined with both LTA and VerifyNow, did not differ with either aspirin or placebo (32.9% ± 2.6% versus 35.8% ± 3.6%, and 33.5 ± 6.4 P2Y12 reaction units (PRU) versus 29.6 ± 5.7 PRU, respectively). Conclusions: Aspirin withdrawal early post‐ACS results in increased platelet reactivity in response to arachidonic acid, despite concomitant treatment with the potent P2Y12 blocker ticagrelor.